Convergence rate of rational spline histopolation - Fischer, Malle; Oja, Peeter (Mathematical Modelling and Analysis, 2007)
The convergence rate of histopolation on arbitrary nonuniform mesh with linear/linear rational splines of class C1 is studied. Established convergence rate depends on Lipschitz smoothness class of the function to histopolate. Corresponding numerical examples are given. First Published Online: 14 Oct 2010